2011
DOI: 10.1080/15257770.2011.597371
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Enhances the Activity of Hypoxanthine-Guanine Phosphoribosyltransferase in Inflammatory Bowel Disease Patients During Low-Dose Thiopurine Therapy: Preliminary Data of an Ongoing Series

Abstract: Thiopurines are crucial in the treatment of inflammatory bowel disease. The phenotype of pivotal metabolic enzymes determines whether thioguanine nucleotides (6-TGN) are generated in clinically sufficiently high levels. The first step in activation of thiopurine prodrugs to 6-TGN is catalysis by hypoxanthine-guanine phosphoribosyltransferase (HGPRT). Often, patients exhibit a clinically unfavorable metabolism, leading to discontinuation of conventional thiopurine therapy. The combination of allopurinol and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…30 The enhanced HGPRT activity corroborates and extends preliminary data. 25 Ding and colleagues recently reported a correlation between the activity of HGPRT and 6-TGN concentrations, which was not observed in this study possibly due the small sample size. 31 Nonetheless, the enhanced HGPRT activity may at least in part explain the rise in 6-TGN concentrations as HGPRT is the first enzyme, responsible for the generation of 6-TGN.…”
Section: 29contrasting
confidence: 40%
“…30 The enhanced HGPRT activity corroborates and extends preliminary data. 25 Ding and colleagues recently reported a correlation between the activity of HGPRT and 6-TGN concentrations, which was not observed in this study possibly due the small sample size. 31 Nonetheless, the enhanced HGPRT activity may at least in part explain the rise in 6-TGN concentrations as HGPRT is the first enzyme, responsible for the generation of 6-TGN.…”
Section: 29contrasting
confidence: 40%
“…Allopurinol inhibits XO but has no direct inhibiting effect on TPMT (8 ). An open-label prospective study of allopurinol combined with lowdose thiopurine therapy showed increased HPRT activity (9 ). This increase in HPRT activity, which catalyzes the first step in 6-TGN production, is consistent with the 6-TGN increase, but it does not fully explain the simultaneous dramatic decrease in 6-MMPR, which leads to an improved metabolite ratio.…”
Section: Discussionmentioning
confidence: 55%
“…However, in the study by van Egmond et al, 19 TPMT activity was not correlated with those who had the highest 6-methyl mercaptopurine levels. Moreover, Seinen et al 24 reported that combination therapy enhanced the activity of HGPRT in patients with IBD. Therefore, it is also possible that the combination of indirect effects of allopurinol on 6-MP metabolism fortuitously results in the shunting of metabolism to avoid hepatotoxicity.…”
Section: Discussionmentioning
confidence: 98%